Zniszczenie Pełzające w Ośrodka Sprężysto-Lepko-Plastycznych - M. Wnuk (Engineering Transactions, 1970)
In the paper are considered progresses dependent on the time and path of load, which take place in the vicinity of the edge of an axially-symmetrical fissure before the occurrence of cracking. In order to obtain an idea of the nonlinear behaviour of plastics in the regions of large stresses and to describe the rheological properties of the material around the fissure we postulate a model which assumes the existence of narrow plastic zones of the Dugdale type, while we assume that the material far from the fissure behaves as a linear visco-clastic medium. In accordance with this model, the limit of plasticity varies with time, as is suggested by Crochet’s equation. This signifies a higher flow pressure with a more rapid load, and conversely. In view of such an assumption, it is possible to describe the first phase of deformations preceding the destruction – namely, the forming of a craze, i.e. a region in which irreversible changes of the mechanical properties and of optical properties occur. This region is formed around the edge of the fissure. Several cases of creeping destruction are considered with different load histories. In particular, the universal equation p0/pG=[K(0)/K(t*)]1/2 is introduced with relates the material strength p0 on the time of duration of the load t*. The characteristic material properties and the length of the fissure are determined by the critical Griffith stress pG, whereas the function K (t) describes the rheological features of plastic. This equation holds for both the three and two-dimensional problems if the ration of the load to the initial yield stress is small. Attention is drawn to the considerable similarity between the universal equation and that derived by Williams for the spherical defect under hydrostatic tension. In  the limiting case, both the theories of fracture – i.e., Griffith’s and Irwins-Orowan’s – results from the theory presented here.